2001
DOI: 10.1590/s1519-566x2001000100025
|View full text |Cite
|
Sign up to set email alerts
|

Flutuação populacional de Diaphorina citri Kuwayama (Hemiptera: Psyllidae) em pomares de citros na região Norte do Estado de São Paulo

Abstract: The purpose of this research was to study the population dynamics of Diaphorina citri Kuwayama in citrus orchards in the north area of Sao Paulo State. The study was carried out in 16 citrus orchards, being six of them in Catanduva area, five in Barretos and five in Monte Azul Paulista. A vacuum sucker machine was used to collect the insects. The highest density of D. citri occurred in the end of the spring time and in the beginning of the summer. During autumn and winter the population was low. Most of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
11

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 3 publications
1
25
0
11
Order By: Relevance
“…A rápida expansão da doença por toda a fazenda deve-se à presença do psilídeo nos pomares o ano todo, e, de acordo com Yamamoto et al (2001), seu pico populacional ocorre na primavera/verão com queda no outono/inverno e, portanto, mesmo nos períodos em que a população do inseto foi baixa, este transmitiu a bactéria das plantas contaminadas para aquelas ainda sadias.…”
Section: Resultsunclassified
“…A rápida expansão da doença por toda a fazenda deve-se à presença do psilídeo nos pomares o ano todo, e, de acordo com Yamamoto et al (2001), seu pico populacional ocorre na primavera/verão com queda no outono/inverno e, portanto, mesmo nos períodos em que a população do inseto foi baixa, este transmitiu a bactéria das plantas contaminadas para aquelas ainda sadias.…”
Section: Resultsunclassified
“…No período chuvoso, houve decréscimo no número de posturas, ovos e ninfas de A. woglumi. Situação inversa foi verifi cada por Yamamoto et al (2001), estudando a fl utuação populacional de Diaphorina citri (Hemiptera: Psyllidae) em pomares de citros do Estado de São Paulo, concluindo que a densidade mais alta do inseto no campo foi no período com maiores precipitações (dezembro e janeiro), e a mais baixa durante o período seco (junho, julho e agosto). Já Dengel (1981) afi rmou que, no início da estação chuvosa, a população de mosca-branca é pequena, mas pode aumentar bruscamente, pois durante o período chuvoso haveria uma fuga do inseto para a parte abaxial da folha; entretanto, como as folhas jovens são preferíveis como alimento, os insetos poderiam voltar nos dias menos chuvosos.…”
Section: Resultsunclassified
“…Deforestation for agriculture and the predominant citrus culture on farms surrounding the state have probably influenced the capture as well as the colonization of sylvatic triatomines in the experimental sentinel sites, because the orange plantations harbor a large number of pests (Yamamoto et al, 2001), such as Diaphorina citri, a Hemiptera, Psyllidae, vector of "greening" or "huanglongbing" (Silva et al, 2009), with a wide geographic distribution, found in citrus crops in the State of São Paulo (Paiva, 2009). This insect occurs mainly in new shoots (Yamamoto et al, 2001), such as those of the crops from the farm next to the site.…”
Section: Discussionmentioning
confidence: 99%
“…This insect occurs mainly in new shoots (Yamamoto et al, 2001), such as those of the crops from the farm next to the site. To prevent their colonization and prevent them from spreading to other farms, the citrus growers perform aerial sprayings with deltamethrin and thimetoxam insecticides (Paiva, 2009) Although chemical control of the environment is not so effective due to climate changes that hinder its residual effect (Dias, 2001), the periodic fumigations made by the farmers in current citrus plantations possibly interfered with the colonization of wild triatomines.…”
Section: Discussionmentioning
confidence: 99%